Influence of Dietary Practices on Class Participation and Learning Outcomes of Boarding Students: A Case of Winneba Senior High School - L., Cobbah (Journal of Home Economics Research, 2024)
This study investigated influence of dietary practices on class participation and learning outcomes of boarding students at Winneba Senior High School (SHS) in the Effutu Municipality of the Central Region of Ghana. Descriptive survey design was adopted for the study. Population composed of all students in the school. Purposive, stratified and simple random sampling techniques were used to select 264 students. Data were collected using questionnaire. Data were analyzed using percentages, means and standard deviation. Findings revealed that majority of the students(X =3.03; SD=2.60) indicated they had poor concentration in class due to their dietary practices while only few students (X =1.99; SD= 1.64) agreed that their dietary practices influenced their memory negatively and for decreased absorption and accuracy rate. The study thus concluded that the students had poor concentration and low interest in class activities due to their dietary practices and recommended that educating the students on the importance of adopting positive dietary practices such as regular breakfast intake and moderate snacking in order to maintain general wellbeing, remain active in class and achieve higher test scores throughout their course period.